Films, literature and culture: Deepa Mehta's elements trilogy - Jain, Jasbir (Jaipur: Rawat Publications, 2007)
Contributed articles on Fire, Earth, and Water, Deepa Mehta's film trilogy; osme originally presented at a seminar in Feb. 2007 organized by IRIS.
Includes bibliographical references.
Keywords: MEHTA, DEEPA 1949 - CRITICISM AND INTERPRETATION - CONGRESSES |; FIRE (MOTION PICTURE) - CONGRESSES; EARTH (MOTION PICTURE: 1998) - CONGRESSES; WATER (MOTION PICTURE: 2005) - CONGRESSES